PEMBENTUKAN KETERAMPILAN ABAD 21 MELALUI PEMBELAJARAN PROJECT BASED LEARNING (PjBL) DENGAN PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN PAI - Al Fithri, Qurrota A'yun; Soraya, Irma; Hamdani, Asep Saepul (Universitas Tribhuwana Tunggadewi, 2024)
This research aims to analyze how project based learning (PjBL) is implemented and its impact in forming 21st century skills, especially in Islamic Religious Education with a contextual approach. This research is library research where the author collects, identifies, analyzes and interprets journals and books that are relevant to the writing topic. Data was analyzed using three stages, namely data condensation, data presentation and conclusion drawing. The results of this paper show that learning in the 21st century has an important role not only in developing cognitive abilities, but also in developing 4C skills. The aim is for students not only to master the knowledge aspect, but also to have competence in the attitude and skill aspects, so that they are ready to compete in the development era of the 21st century. Overall, PjBL not only helps students understand the material in depth but also trains 21st century skills, namely critical thinking, communication, collaboration and creativity. Apart from that, the integration of PjBL with a contextual approach makes learning Islamic Religious Education more meaningful, because students can relate the lesson material to Islamic religious values that are applied in everyday life.